Religious Leaders' Understanding of Astronomy and Its Implications in Determining the Direction of the Qibla in Medang Daras District, Batubara Regency - Ihsan Asupi; Dhiauddin Tanjung (Lambung Mangkurat Law Journal, 2025)
The direction of the qibla is a fundamental aspect of Islamic worship, as facing the Kaaba is a legal requirement for the validity of prayer. Errors in determining the qibla direction, therefore, have normative implications in Islamic law. This study examines the understanding and practice of religious leaders in Medang Deras District, Batu Bara Regency, in determining the qibla direction from both legal and astronomical perspectives. Using a qualitative descriptive method, the research explores primary data obtained through interviews and direct observation, complemented by secondary data from literature and scientific references related to astronomy and Islamic law. The findings indicate that the understanding of religious leaders regarding astronomical principles remains limited, resulting in practical methods that rely heavily on local traditions such as aligning with the direction of the sunset or following the guidance of elder community members. This practice shows a discrepancy between local customary understanding and the normative standards of Islamic law, which require accuracy in facing the qibla. Therefore, strengthening legal and astronomical literacy among religious leaders is essential to ensure the precision of qibla determination and the validity of worship practices in accordance with sharia principles.